The factors affecting unsold residential unit from public perspective in Kinta, Perak / Anis Anisah Hashim - Hashim, Anis Anisah (2023)
This academic project's research investigates the factors affecting unsold residential units from public perspective in Kinta, Perak. The issue of unsold residential units always came up. Malaysians might be clueless about this issue that is always addressed every year. Certain people in Malaysia might know why these things happen, but most people are still clueless. NAPIC reports a 3.3% rise in residential unit dumping from 2020 to 2019. More than 2,900 units remain unsold in Perak. Residential units that are still unfinished in 2021 show a large increase of 2,233 units compared to 854 units in 2020, which indicates an increase in the number of unsold residential units. The state with the fourth-highest number of unsold properties in 2020 is Perak. Therefore, this research is conducted to find the factors that affecting unsold residential units in Kinta, Perak. There are two objectives in this research: the first objective is to identify the factors affecting unsold residential units in Perak, and the second objective is to rank the factors affecting unsold residential units in Kinta, Perak. The first objective is gathered from the literature review.